Densification of cancellous bone with autologous particles can enhance the primary stability of uncemented implants by increasing the interface friction coefficient. (June 2022) - Zobel, Sebastian M.; Ruhr, Miriam; Neumann, Fenna; Huber, Gerd; Morlock, Michael M.
Abstract: Sufficient primary stability is one of the most important prerequisites for successful osseointegration of cementless implants. Bone grafts, densification and compaction methods have proven clinically successful, but the related effects and causes have not been systematically investigated. Postoperatively, the frictional properties of the bone-implant interface determine the amount of tolerable shear stress. Frictional properties of different implant surfaces have been widely studied. Less attention has been paid to the influence of host bone modifications. The purpose of this study was to investigate the influence of densification of cancellous bone with bone particles on the interface friction coefficient. Cancellous bone samples from femoral heads were densified with bone particles obtained during sample preparation. The densification was quantified using micro-Ct. Friction coefficients of the densified and paired native samples were determined. Densification increased the BV/TV in the first two millimeters of the bone samples by 10.5 ± 2.7 % to 30.5 ± 2.7 % (p < 0.001). The static friction coefficient was increased by 10.5 ± 6.1 % to 0.43 ± 0.03. The static friction coefficient increased with higher BV/TV of the bone interface, which is represented by the top 2 mm of the bone. The increase in contact area, intertrabecular anchorage and particle bracing could be responsible for the increase in friction. Optimization of particle shape and size based on the patient's individual bone microstructure could further increase frictional resistance. Bone densification has the potential to improve the primary stability of uncemented implants.